Pengaruh Profesionalisme, Budaya Organisasi dan Komitmen Organisasi pada Kinerja Auditor - Prabayanthi, Putu Ayu; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p09, 2018)
Public accounting profession is a profession of public trust, so the role of auditors is very important in helping improve the performance of public accountants to become more qualified. This study aims to obtain empirical evidence on the influence of professionalism, organizational culture and organizational commitment to auditor performance. This research was conducted at Public Accounting Fir m  in Bali Province registered with Indonesian Institute of Certified Public Accountant   in 2016. Data collection method used in this research is survey method with questionnaire technique. The population in this study is as many as 60 people. Sampling method used is nonprobability sampling method. Data analysis used is multiple linear regression analysis. The result shows that the variables of professionalism, organizational culture and organizational commitment have a positive effect on auditor performance. This shows that the higher professionalism, organizational culture and organizational commitment owned by an auditor, the higher the auditor's performance. Keywords : Professionalism, organizational culture, organizational commitment, auditor performance